CaRpools: an R package for exploratory data analysis and documentation of pooled CRISPR/Cas9 screens - Winter, Jan; Breinig, Marco; Heigwer, Florian; Brügemann, Dirk; Leible, Svenja; Zhan, Tianzuo; Boutros, Michael (Bioinformatics, 2016)
Motivation: Genetic screens by CRISPR/Cas9-mediated genome engineering have become a powerful tool for functional genomics. However, there is currently a lack of end-to-end software pipelines to analyze CRISPR/Cas9 screens based on next generation sequencing. Results: The CRISPR-AnalyzeR for pooled screens (caRpools) is an R package for exploratory data analysis that provides a complete workflow to analyze CRISPR/Cas9 screens. To further support the analysis of large-scale screens, caRpools integrates screening documentation and generation of standardized analysis reports. Availability and implementation: caRpools, manuals and an open virtual appliance are available at http://github.com/boutroslab/caRpools .